2009
DOI: 10.1002/ir.287
|View full text |Cite
|
Sign up to set email alerts
|

Effectively involving faculty in the assessment of student engagement

Abstract: This chapter discusses four roles—source of data, audience, data analyst, and beneficiary of assessment knowledge—faculty can play in the assessment of student engagement on college and university campuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…To rise to the call in developing engaging learning environments (Roberts et al, 2016), faculty members should consider utilizing the CLASSE instrument, or similar instruments, to determine discrepancies between student-reported and instructorvalued engagement activities. The localization of engagement data can serve as a useful supplement to other course evaluations (Laird, Smallwood, Niskodé-Dossett, & Garver, 2009). In objective one, instructors with educative responsibilities for the AGEDS 450 provided the value (importance) placed on specific engagement activities.…”
Section: Conclusion and Discussionmentioning
confidence: 44%
“…To rise to the call in developing engaging learning environments (Roberts et al, 2016), faculty members should consider utilizing the CLASSE instrument, or similar instruments, to determine discrepancies between student-reported and instructorvalued engagement activities. The localization of engagement data can serve as a useful supplement to other course evaluations (Laird, Smallwood, Niskodé-Dossett, & Garver, 2009). In objective one, instructors with educative responsibilities for the AGEDS 450 provided the value (importance) placed on specific engagement activities.…”
Section: Conclusion and Discussionmentioning
confidence: 44%
“…The localization of engagement data can serve as a useful supplement to other course evaluations as well (Laird, Smallwood, Niskodé-Dossett, & Garver, 2009).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The value of educational activities varies across and within faculty, making any resulting data from institution-wide examinations of student engagement difficult to interpret; while classroom-level examinations of student engagement allow for localization of variation in student engagement (Smallwood, 2008). Laird, Smallwood, Niskodé-Dossett, and Garver (2009) noted the assessment of student engagement is often conducted by informal means (i.e., taking attendance or observing student behaviors), and further discussed the utility of a class-specific measure of student engagement instrument for improving course design. Marx et al (2016) identified a gap in localized engagement data and the importance of describing "…the perceived engagement of undergraduate students…" (p. 213).…”
Section: Purpose and Objectivesmentioning
confidence: 99%
“…Over the years, the NSSE has acquired a reputation for being a prominent, formal assessment tool that facilitates the studying of student engagement at four-year colleges and universities (Nelson Laird, Smallwood, Niskode-Dosset, & Garver, 2009). This survey provides institutions with information about how students use resources at their particular institution to assist improvement efforts (Kuh, 2001a).…”
Section: Background Of the Nssementioning
confidence: 99%
“…The NSSE allows institutions to receive information about student engagement at the institutional level, which helps determine how well the institution fosters student learning (Kuh, 2003). Since its inception, NSSE has acquired a reputation for being a prominent, formal assessment tool that facilitates the studying of student engagement at four-year colleges and universities (Nelson Laird, Smallwood, Niskode-Dosset, & Garver, 2009).…”
Section: Chapter One: Introdution Overviewmentioning
confidence: 99%